Budowanie kariery jako proces inwestycji w portfolio - Cybal-Michalska, Agnieszka (Studia Edukacyjne, 2016)
Multicontextual social changes imply definitely new ways of interpretation and determine reflections about the condition of contemporary humans, including the human being as “a manager” of his own career. A society has become an area where individuals can show their initiative. A contemporary study of careers demands the inclusion of multicontextual changes in the job world. These changes face employees with new requirements. The most important ones are the increase of the role attached to a career and the ability to plan, manage and monitor one’s own career in a lifelong perspective. Considerations about a career cannot leave out the issue of the subjective sense that an individual finds in one’s own career in the context of possibilities that a man can have a satisfactory career. The world of careers is a world of numerous micro-changes. In the “portfolio” of micro-changes, the time between changes is reduced and after a period of stability renewed separation comes increasingly quickly.